2009
DOI: 10.1007/s11010-009-0226-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction of RIP-2 kinase by proinflammatory cytokines is mediated via NF-κB signaling pathways and involves a novel feed-forward regulatory mechanism

Abstract: The transcription factor NF-kappaB (nuclear factor kappaB) is a central mediator of inflammatory and apoptotic signaling in the cell. The protein kinase RIP-2 is a member of the CARD protein family (caspase activation and recruitment domain, also known as CARD3, Ripk2, CARDIAK, RICK, and CCK), and has been shown to be an activator of NF-kappaB. In this study, it was demonstrated by transcriptional profiling and protein expression analysis that the inflammatory cytokines TNF-alpha, IL-1 beta, and IFN-gamma indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Various strategies targeted at the NF-kB signaling pathway, such as NF-kB-specific decoy oligonucleotide (19), p65-specific antisense oligonucleotide (20), and IKKb-selective small molecule inhibitor (21), have demonstrated beneficial effects in experimental asthma models. Rip2 is not only a transcriptional product of NF-kB, but also a positive regulator of NF-kB activity (12). In this study, to our knowledge, we observed for the first time that lung Rip2 protein level was markedly elevated in experimental asthma, which was accompanied by increased NF-kB nuclear translocation and DNA binding.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Various strategies targeted at the NF-kB signaling pathway, such as NF-kB-specific decoy oligonucleotide (19), p65-specific antisense oligonucleotide (20), and IKKb-selective small molecule inhibitor (21), have demonstrated beneficial effects in experimental asthma models. Rip2 is not only a transcriptional product of NF-kB, but also a positive regulator of NF-kB activity (12). In this study, to our knowledge, we observed for the first time that lung Rip2 protein level was markedly elevated in experimental asthma, which was accompanied by increased NF-kB nuclear translocation and DNA binding.…”
Section: Discussionmentioning
confidence: 51%
“…Rip2 has been shown to mediate TCR signaling to NF-kB activation, cytokine production, and T cell proliferation, but the serine/threonine kinase activity is not required for NF-kB response (9)(10)(11). Rip2 is an inducible transcriptional product of NF-kB activation, and serves as a positive regulator of NF-kB pathway by binding to the IKK complex (12). In vitro study revealed that overexpression of Rip2 in HEK293T cells increases NF-kB activity and IL-1b production (13).…”
mentioning
confidence: 99%
“…It contains a serine/threonine kinase domain and a caspase activation and recruitment domain (35). It can be recruited to TNFR1 via TRAF proteins and can activate caspases and NFB signaling (36,37). Although RIP2 phosphorylation at 10 min did not correlate well with apoptosis, it did correlate with both p38 phosphorylation (r ϭ 0.90, p Ͻ 0.0001) and JNK phosphorylation (r ϭ 0.87, p Ͻ 0.0001), and RIP2 has previously been shown to lie upstream of these proteins mechanistically (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…Immunopharmacological intervention against atherosclerosis attracts major interest. Rip2 recently has been suggested to be a key target for immune intervention to atherosclerosis, 19 as well as several other pathological disorders. 36,37 However, the results of the present study clearly demonstrate that immunosuppression targeting Rip2 may have unexpected negative consequences, eg, subendothelial lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…14 -18 Furthermore, it was demonstrated recently that the regulation of Rip2 involves a novel feedforward regulatory mechanism: Rip2 not only positively regulates NF-B activity, but inflammatory cytokines that activate the NF-B pathway induce increased Rip2 expression. 19 These studies thus suggest the therapeutic potential of inhibiting Rip2 to inhibit inflammation and thus protect against the development of atherosclerosis. …”
mentioning
confidence: 96%